PENGARUH CITRA MEREK DAN KEPERCAYAAN MEREK TERHADAP LOYALITAS PELANGGAN PENGGUNA AIR MINUM KEMASAN MEREK AQUA - Hanifa Nurfadila; Muhammad Reza Anwar Nurdin (Jurnal Ekonomi dan Industri, 2022)
The type of approach in this research is a quantitative approach. The sample in this study was the community of 1rd neighbourhood, 4th hamlet, Kranji Village, West Bekasi District.. The sampling technique used is the slovin. The data collection method is using primary data including observation questionnaires and interviews. The data analysis technique used instrument data test, classical assumptions, hypothesis testing, and multiple linear regression. From the results of tests found the fact that brand image and brand trust simultaneously have a significant effect on consumer loyalty. In addition, brand image and brand trust also partially have a significant effect on consumer loyalty.